Kandungan Hemiselulosa Pada Serat Kasar Eceng Gondok (Eichhornia crassipes): Hemicellulose Content in The Crude Fiber of Water Hyacinth (Eichhornia crassipes) - Fatmawati; Syauqi, Ahmad; Ramadhan, Majida (Jurnal SAINS ALAMI (Known Nature), 2023)
Water hyacinths can proliferate, so efforts are needed to deal with them so as not to disturb and damage the environment. The cell wall of hyacinth plants contains lignocellulose. This study aims to determine the number of hemicellulose molecules from the hydrolysis results of the presence of a component of the crude fibre of hyacinth (Eichhornia crassipes). The methods used in this study were the Wendee crude fibre analysis method and the Chesson-Datta method of hemicellulose hydrolysis. The study used quantitative descriptive methods. The analysis results of hyacinth crude fibre in every 1 gram of dried hyacinth powder contain an average crude fibre weight containing minerals in the leaves of 30.9% and 48.6% in the roots. Hydrolysis of hemicellulose obtained the average hemicellulose contained in hyacinth leaves at 11.2% and roots at 19.7%.  Keywords: Hyacinth, Crude fiber, Hemicellulose ABSTRAK Eceng gondok dapat tumbuh dengan cepat, sehingga diperlukan upaya untuk menanganinya agar tidak mengganggu dan merusak lingkungan. Dinding sel tanaman eceng gondok mengandung lignoselulosa. Tujuan dari penelitian ini untuk mengetahui kuantitas molekul hemiselulosa dari hasil hidrolisis pada keberadaan komponen serat kasar eceng gondok (Eichhornia crassipes). Metode yang digunakan dalam penelitian ini yaitu metode analisis serat kasar Wendee dan hidrolisis hemiselulosa metode Chesson-Datta. Penelitian menggunakan metode deskriptif kuantitatif. Hasil analisis serat kasar eceng gondok dalam tiap 1gram serbuk eceng gondok kering mengandung rata-rata berat serat kasar terkandung mineral pada daun 30.9% dan 48,6% pada akar. Hidrolisis hemiselulosa didapatkan rata-rata hemiselulosa yang terkandung dalam daun eceng gondok 11,2% dan akar 19,7%. Kata kunci: Eceng gondok, Serak Kasar, Hemiselulosa